(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The Misery of orphans had the concern of pre-Islamic and veteran poets. Thus, it’s different figures have been presented in several contexts of their poetry, but it hasn’t got the same concern from researchers as it has got from the great poets. So this research is fossicking for the semantic and figures of orphan. And is witnessing it’s turning into symbols which the controlling presence in some contexts, themselves is in graining. In addition to the repetition which stimulates the outlook of its semantic and unveil the purposes of poets. Thus, it is studying the orphan’s symbols and its semantic in different situations of pity, pride, praise, and bluster. It’s also analyzing and comparing them paying attention to explaining them in their two dimensions the artistic and the intellectual.